A tripartite synergistic optimization strategy for zinc-iodine batteries - Weibin Yan; Ying Liu; Jiazhen Qiu; Feipeng Tan; Jiahui Liang; Xinze Cai; Chunlong Dai; Jiangqi Zhao; Zifeng Lin (Nature Communications)
Abstract The energy industry has taken notice of zinc-iodine (Zn-I2) batteries for their high safety, low cost, and attractive energy density. However, the shuttling of I3 − by-products at cathode electrode and dendrite issues at Zn metal anode result in short cycle lifespan. Here, a tripartite synergistic optimization strategy is proposed, involving a MXene cathode host, a n-butanol electrolyte additive, and the in-situ solid electrolyte interface (SEI) protection. The MXene possesses catalytic ability to enhance the reaction kinetics and reduce I3 − by-products. Meanwhile, the partially dissolved n-butanol additive can work synergistically with MXene to inhibit the shuttling of I3 −. Besides, the n-butanol and I− in the electrolyte can synergistically improve the solvation structure of Zn2+. Moreover, an organic-inorganic hybrid SEI is in situ generated on the surface of the Zn anode, which induces stable non-dendritic zinc deposition. As a result, the fabricated batteries exhibit a high capacity of 0.30 mAh cm−2 and a superior energy density of 0.34 mWh cm−2 at a high specific current of 5 A g−1 across 30,000 cycles, with a minimal capacity decay of 0.0004% per cycle. This work offers a promising strategy for the subsequent research to comprehensively improve battery performance.